1991
DOI: 10.1159/000195915
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Low-Dose Administration of Erythromycin to Patients with Diffuse Panbronchiolitis

Abstract: Although diffuse panbronchiolitis (DPB) has carried a poor prognosis, long-term low-dose administration of erythromycin (EM) is very effective. We administered EM at a daily dose of 400–600 mg to 19 DPB subjects for more than 2 months. Sixteen subjects were relieved from productive cough and dyspnea, and their chest X-ray pictures were improved. We performed a pharmacokinetic study of EM in 11 DPB subjects (8 re-sponders; 3 nonresponders) after the long-term low-dose administration. The maximal serum and sputu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
156
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(162 citation statements)
references
References 10 publications
5
156
1
Order By: Relevance
“…While DPBhas a poor prognosis, the long-term administration ofa low dose oferythromycin can provide benefit (3)(4)(5)(6). Interestingly, such a low dose oferythromycin rarely eradicates pathogens from the lower respiratory tract, unlike the conventional doses used in treating an acute exacerbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While DPBhas a poor prognosis, the long-term administration ofa low dose oferythromycin can provide benefit (3)(4)(5)(6). Interestingly, such a low dose oferythromycin rarely eradicates pathogens from the lower respiratory tract, unlike the conventional doses used in treating an acute exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prognosis of DPBis poor, Kudoh et al (3) reported that the long-term administration of low doses of erythromycin, a 14-membered ring macrolide, is highly effective in improving the clinical symptoms, pulmonary dysfunction, and hypoxia in this disorder (4)(5)(6). These benefits were obtained without the eradication of bacteria from the sputum such as Pseudomonasaeruginosa, which is resistant to erythromycin.…”
Section: Introductionmentioning
confidence: 99%
“…11,37 Macrolides have been shown to improve outcome in panbronchiolitis. 38,39 Their beneficial effects are considered to be due to their anti-inflammatory rather than anti-bacterial activities. [40][41][42] Although there has been no report of macrolide use in BO, their mechanisms of action and relatively minor adverse effects warrant a clinical trial.…”
Section: Treatmentmentioning
confidence: 99%
“…We do know that the antibacterial action of the erythromycin against the usual isolated organisms from cultures of sputum of DPB patients (H. influenza and P. aeruginosa) could not be considered as an important mechanism, since the concentration of erythromycin in sputum and serum (with the usual dose of 600 mg daily) are very far below the minimum inhibitory concentration required for these organisms 21 . In spite of this, the use of low dose, long-term macrolide treatment figures as the one with large number of studies showing clinical, functional, and radiological improvement 8,16,[22][23][24] , as well as reduction in the mortality rate 25 .…”
Section: Discussionmentioning
confidence: 99%